2006
DOI: 10.1136/ip.2006.012658
|View full text |Cite
|
Sign up to set email alerts
|

Homicide of children aged 0–4 years, 2003–04: results from the National Violent Death Reporting System

Abstract: Introduction:To better understand, and ultimately prevent, infant/child homicide, it is imperative to more thoroughly elucidate the circumstances and conditions related to such instances. Data were obtained from the US National Violent Death Reporting System (NVDRS) to illuminate circumstances related to homicide among children aged 4 years or less, and to identify demographic groups which may be at increased risk.Methods:The NVDRS is an active surveillance system that provides comprehensive information on all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 17 publications
(9 reference statements)
5
37
1
3
Order By: Relevance
“…Excluding those deaths related to but not directly caused by maltreatment, the average is 34.5 cases (0-17 years) per year (0.31 per 100,000 per year) or 20.5 cases (0-4 years) per year (0.67 per 100,000 per year). These figures are considerably lower than those reported for 0-4 year olds in the United States (2.5 -3.0 per 100,000 per year) (Bennett, et al, 2006) and slightly lower than the 1-2 cases per week previously estimated by Green (Green, 1998), but still equates to around one child per week dying in England as a consequence of child abuse or neglect.…”
Section: Discussioncontrasting
confidence: 66%
“…Excluding those deaths related to but not directly caused by maltreatment, the average is 34.5 cases (0-17 years) per year (0.31 per 100,000 per year) or 20.5 cases (0-4 years) per year (0.67 per 100,000 per year). These figures are considerably lower than those reported for 0-4 year olds in the United States (2.5 -3.0 per 100,000 per year) (Bennett, et al, 2006) and slightly lower than the 1-2 cases per week previously estimated by Green (Green, 1998), but still equates to around one child per week dying in England as a consequence of child abuse or neglect.…”
Section: Discussioncontrasting
confidence: 66%
“…The NVDRS, which is currently active in approximately one-third of the states, collects data on fatalities associated with child maltreatment and has potential synergy with CFRTs. 28 CFRTs support the public health approach of using data collection or surveillance to define the issues; identify risk factors, protective factors, and barriers within individual families and the greater community; develop interventions that are based on analysis; implement interventions at the community level; and use evaluation results to modify and improve the initial interventions. 16 …”
Section: Establishment Of Cfrtsmentioning
confidence: 99%
“…Despite the inaccuracies that may be involved in coding AHT cases, previous studies have reported potential risk factors for AHT in young children, including demographic, socioeconomic, and clinical. 3,6,8,14 According to several studies, infants younger than 1 year and with a lower socioeconomic status are at higher risk for AHT. 6,14 Additionally, a higher risk of AHT has been documented among specific racial and/or ethnic minorities.…”
mentioning
confidence: 99%
“…6,14 Additionally, a higher risk of AHT has been documented among specific racial and/or ethnic minorities. 3,8 Clinical entities associated with AHT include retinal hemorrhages and subdural hematomas. 9,28 Although pertinent information has been obtained from studies published to date, most of these studies have significant limitations, for example, small sample sizes, hospital-specific characteristics, and an inability to generalize findings to infants nationwide.…”
mentioning
confidence: 99%